2021
DOI: 10.3390/buildings11090418
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of Museum Architecture, Spaces and Exhibits on Virtual Visitors Using Facial Expression Analysis Software

Abstract: Since the launch of online video portals in 2005, museums have encouraged visitors to upload and share their visits online. Although much has been written about visitors’ experiences in museums, very little exists on the impact virtual visits have on viewers. In this qualitative pilot study, a total of 2035 emotional reactions were recorded and analyzed after visiting 14 online museums using a facial expression recognition software. Following open and axial coding techniques, themes and subcategories emerged. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…There have been many experiments using video cameras and facial expression recognition software to study human emotional responses in different environments [177]. For example, analyzing the effect of virtual museum tours on visitors' emotions by recording facial expression signals revealed that online museum experiences can be as engaging as physical tours [49]. Facial expression recognition technology has also been used to explore the effects of glass-framed buildings on human responses and psychological comfort, showing that glass structures can create a comfortable and positive emotional environment [178].…”
Section: Behavioral Datamentioning
confidence: 99%
“…There have been many experiments using video cameras and facial expression recognition software to study human emotional responses in different environments [177]. For example, analyzing the effect of virtual museum tours on visitors' emotions by recording facial expression signals revealed that online museum experiences can be as engaging as physical tours [49]. Facial expression recognition technology has also been used to explore the effects of glass-framed buildings on human responses and psychological comfort, showing that glass structures can create a comfortable and positive emotional environment [178].…”
Section: Behavioral Datamentioning
confidence: 99%
“…The "Communicational" indicator comprises aspects related to the dissemination of the exhibition, the provision of instructions, and the diversity of media and assistive technology resources needed. One of the innovations brought to museums' exhibitions by the development of the web environment is the possibility to promote a multisensory multimedia activity, with almost unlimited information connections, an aspect that can contribute to the emotional experience and the sense of "being present" of the visitor (Nubani & Öztürk, 2021;Sylaiou et al, 2010). In contrast, museums often offer a limited experience in exploring different media and must reflect on the dependence of a single sensory stimulation, usually visual, and written communication, to interact with audiences (Papadimitriou et al, 2016).…”
Section: Accessibility Indicators For Online Exhibitions and Museumsmentioning
confidence: 99%